2022
DOI: 10.1136/thoraxjnl-2021-218196
|View full text |Cite
|
Sign up to set email alerts
|

Routine lung volume recruitment in boys with Duchenne muscular dystrophy: a randomised clinical trial

Abstract: BackgroundImpaired cough results in airway secretion retention, atelectasis and pneumonia in individuals with Duchenne muscular dystrophy (DMD). Lung volume recruitment (LVR) stacks breaths to inflate the lungs to greater volumes than spontaneous effort. LVR is recommended in DMD clinical care guidelines but is not well studied. We aimed to determine whether twice-daily LVR, compared with standard of care alone, attenuates the decline in FVC at 2 years in boys with DMD.MethodsIn this multicentre, assessor-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
(81 reference statements)
4
18
0
Order By: Relevance
“…Our team's recent randomized trial of LVR using a self-inflating resuscitation bag with a one-way valve reported an adherence rate of 41% over 2 years. 11 Similar adherence rates (31%-60%) have been reported in studies evaluating alternative preventive respiratory therapies aimed at maintaining cough strength, such as mechanical insufflationexsufflation. [12][13][14] There is a need to better understand factors that promote or impede the use of LVR, to facilitate its implementation into clinical care and ensure optimal outcomes.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our team's recent randomized trial of LVR using a self-inflating resuscitation bag with a one-way valve reported an adherence rate of 41% over 2 years. 11 Similar adherence rates (31%-60%) have been reported in studies evaluating alternative preventive respiratory therapies aimed at maintaining cough strength, such as mechanical insufflationexsufflation. [12][13][14] There is a need to better understand factors that promote or impede the use of LVR, to facilitate its implementation into clinical care and ensure optimal outcomes.…”
Section: Introductionsupporting
confidence: 63%
“…Previous studies have demonstrated benefits of LVR in slowing lung function decline and maintaining cough efficacy in individuals with advanced neuromuscular disease 4–7 . Clinical care guidelines recommend regular use of LVR when cough strength is impaired, 2,8–10 though there is clinical equipoise regarding optimal timing of introduction 11 …”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies have focused on respiration, focusing on surface electromyography of respiratory muscles, respiratory physiological function, quality of life, and mood, while few observations have been made to improve sound quality or loudness. This study focused on the use of computer analysis-based sound spectrum analysis to observe the improvement of sound quality in CSCI patients with music therapy ( Tamplin et al, 2013 ; Katz et al, 2022 ). In this study, the researchers used a meticulous and professional music intervention method to improve the sound quality of CSCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the control group were given respiratory phonation training (RPT). RPT is a vocal training method whereby respiratory physiotherapists use physical therapy techniques to press the abdominal cavity with external force after the patient inhales to help them produce long sounds ( Katz et al, 2022 ). Patients in the intervention group were treated by music therapy professionals using VIT techniques.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…This highly abbreviated historical perspective suggests an unequivocal success story, but it omits remaining knowledge gaps. The article by Katz et al in Thorax 9 is directed at one of those gaps—a lack of randomised, controlled trials. Such studies are needed if the component therapies of respiratory management—and the threshold levels of weakness at which they are implemented—are to be based on high-quality scientific evidence, rather than clinical experience and expert opinion.…”
mentioning
confidence: 99%